Sonochemical degradation of triclosan, benzophenone-1 and benzophenone -3 in Water (2018)
RESUMEN: Degradation of triclosan, benzophenone 1, and benzophenone 3 by multifrequency ultrasound was studied at high frequencies. Frequency effect on initial degradation rates was analyzed and an optimum frequency was found. Power density effect was also analyzed. A reaction mechanism was proposed and reaction kinetics were found. Pulsed US mode effect was analyzed too. Simultaneous analysis of the effect of power, frequency, pulse time, and silent time was made and optimization by response surface methodology was made for benzophenone 3 degradation. Analysis of this and radical scavengers, let conclude if degradation of molecules was taking place in the bubble/liquid interface, bubble, or bulk liquid. Toxicity tests were conducted by Microtox®. Degradation byproducts and degradation pathways were proposed.